PENGARUH CITRA MEREK, HARGA, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK KOSMETIK SARIAYU DI KELURAHAN RANGKAPAN JAYA BARU, DEPOK - Ananda Chairunnisa, - (2019)
This study is a quantitative study aims to know the effect of the brand image, the price, and quality product toward buying decision. The population of this study is the society of district Rangkapan Jaya Baru, Depok. The sample was conducted for 75 respondents. The methodology of this study is non-probability sampling, especially purposive sampling. The data was collected by distributing the questionnaire. This study analyzed using PLS (Partial Least Square) analysis technique. The result of this study showed that (1) the brand immage significantly affect the buying decision with the coefficient percentage as big as 0,258. (2) the price significantly affect the buying decision with the coefficient percentage as big as 0,746. (3) the product quality did not significantly affect the buying decision with the coefficient as big as 0,005.